Pengaruh Digitalisasi terhadap Kinerja Keuangan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Fortuna, Wines; Helmy, Herlina (Universitas Negeri Padang, 2025)
This study aims to empirically examine the effect of digitalization on financial performance and analyze the moderating role of firm size. It also addresses gaps in prior studies by considering organizational capacity in adopting digital technology. The sample consists of 126 financial sector companies listed on the Indonesia Stock Exchange for the 2022–2023 period, selected through purposive sampling. The findings reveal that digitalization negatively affects financial performance, suggesting that not all technology investments lead to immediate benefits. However, firm size positively moderates this relationship. According to the Resource Based View (RBV) theory, larger firms possess greater resources and capabilities to manage digital initiatives effectively.